Let’s (not) talk about race: comparing mock jurors’ verdicts and deliberation content in a case of lethal police use of force with a White or Indigenous victim - Ewanation, Logan (Psychology, crime & law, 2026)
Several lethal police use of force (UoF) encounters have recently occurred across North America, sparking public debate about officer accountability. This project investigated what jurors discuss during deliberations in simulated trials involving UoF and evaluated whether the race of the victim affects individual verdicts and deliberation content. Canadian jury-eligible participants (N = 78) watched and listened to a fictional trial involving a police officer charged with manslaughter with a White or Indigenous victim. After rendering individual pre-deliberation verdicts, mock jurors took part in a 60-minute deliberation session, then rendered individual post-deliberation verdicts. Although victim race did not have a statistically significant effect on pre-deliberation verdicts, the odds of jurors rendering a guilty post-deliberation verdict was nearly 10 times higher when the victim was White as opposed to Indigenous. Deliberation analyses indicated that jurors were significantly more likely to provide ‘anti-defendant’ and ‘pro-prosecution’ utterances when the victim was White as compared to Indigenous. However, jurors very rarely directly discussed race in deliberations. Additionally, jurors with negative perceptions of police were significantly more likely to utter ‘anti-defendant’ statements. Overall, this study suggests that, contrary to the assumption of the Canadian legal system, victim race influences legal decision-making in trials involving officer UoF.